A nexus between renewable energy, FDI, oil prices, oil rent and CO2 emission: panel data evidence from G7 economies. (4th February 2022) - Royal, Saransh; Singh, Kamaljit; Chander, Ramesh
Abstract: Volatile energy prices, supply chain vulnerability and ecological implications of depleting fossil fuels have obligated the nations to swap carbon energy resources with sustainable and consumption energy choices. The study aims to investigate the sustaining connection of renewable energy consumption with trade openness, oil rent (OR), oil prices (OP) and carbon dioxide emissions of the G7 nations over the period 1971–2019. Using FMOLS and DOLS approach to panel data for analysing the long‐run elasticity, and SUR for estimating the short‐run elasticities. The analysis outcomes suggested that in the long run, a rise in Foreign Direct Investment (FDI) incursion and OP and OR are found to be major drivers of renewable energy consumption. The long‐term elasticity was estimated from a panel co‐integrated FMOLS and DOLS model are mostly alike and present an encouraging association among different variables. Surprisingly, the average number of years to return to equilibria turned out to be 16 years, which is precisely in line with the voluntary commitment by G7 for overall net‐zero electricity emission by 2035. The findings reported in the study suggest the oil‐producing countries should be compensated to diversify energy production. Higher OR is desired to further strengthen the renewable energy generation and consumption as implied by the findings reported. FDI may also further be welcomed in greener know‐hows for sustainable green energy choices.